2005
DOI: 10.1080/09638280500076384
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of pressure sore prevention using a computerized mattress system in patients with spinal cord injury

Abstract: The economic evaluation indicates that the computerized mattress system is advisable for patients with SCI who require assistance for repositioning, but its profitability depends on the employment terms of the nursing manpower. In addition, other possible alternative pressure management systems should be examined, and additional research may be needed to determine the optimal combination of such systems for a spinal cord rehabilitation department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Nineteen of these articles provided original data with clear descriptions of interventions, study methods, and the economic outcomes considered and were included in the narrative review. 3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] They are summarized in Tables 1 and 2. Two systematic reviews were also identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen of these articles provided original data with clear descriptions of interventions, study methods, and the economic outcomes considered and were included in the narrative review. 3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] They are summarized in Tables 1 and 2. Two systematic reviews were also identified.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies provided economic evaluations (5 costeffectiveness, 3 cost-benefit, 2 both) of approaches to the prevention of PIs. [15][16][17][18][19][20][21][22][23][24] Favorable outcomes from a bundle of PI prevention strategies were found in 2 studies that based cost estimates on statistical modeling using data from the literature. 15,16 A combination of risk assessment, nutritional support, and repositioning resulted in an estimated net savings of Can $55.12 per patient per day, a 9.3% decrease in PI incidence, and a 0.47% reduction in deaths in 2013.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations